Validity and reliability of the Chinese version of the Normalization MeAsure Development(NoMAD) - Mengyao Jiang; Qing Wang; Tracy Finch; Dongli She; Yujun Zhou; Yuet Foon Chung; Jie Chen; Lin Han (BMC Health Services Research, 2022)
Abstract Background The Normalization MeAsure Development (NoMAD) is a brief quantitative tool based on the Normalization Process Theory (NPT), which can measure the implementation process of new technologies and complex interventions. The aim of our study was to translate and culturally adapt the NoMAD into Chinese, and to evaluate the psychometric properties of the Chinese version of NoMAD. Methods According to the NoMAD translation guideline, we undertook forward translation, backward translation, and compared these translations to get a satisfactory result, then we performed cognitive interviews to achieve cross-culture adaptation. And the psychometric properties of the final version were evaluated among clinical nurses who used the pressure injuries management system via WeChat mini-program at a tertiary hospital in northwestern China. Results A total of 258 nurses were enrolled in our study, and the response rate was 92.1%. The Cronbach’s alpha of four dimensions were as follow: Coherence (0.768), Cognitive Participation (0.904), Collective Action (0.820), and Reflexive Monitoring (0.808). The overall internal consistency was 0.941. The confirmatory factor analysis results showed a good fit for its theoretical structure (CFI = 0.924, TLI = 0.910, RMSEA = 0.0079, SRMSR = 0.046, χ2/df = 2.61). The item-level content validity index ranged from 0.857 to 1, and the scale-level content validity index was 0.95. There were positive correlations between four constructs scores and three general normalization scores. Conclusions The Chinese version of NoMAD is a reliable and valid tool to evaluate the implementation process of innovations.